Remembering and Forgetting the Korean War in the Republic of Korea - Hyeon Ju Lee (Suomen Antropologi, 2023)
The Korean War had no official ending and has continued in a form of Cold War since 1953, the year the cease-fire agreement was signed, and yet, during the  past five decades, it appears to have faded from South Korean memory. Anti-communism became a national ideology in post-war South Korea. For a country that was endeavoring to establish a national identity that differs from communist North Korea, the establishment of an anti-communist state was inevitable. However, the collapse of the Communist Bloc and a humanitarian crisis in North Korea in the 1990s led to attitudinal changes in the South Korean public toward North Korea. The forgetting and remembering of North Korea in conjunction with the memory of the Korean War has left the South Korean people ambivalent toward North Koreans. This paper explores social encounters between North and South Koreans in the late 2000s in Seoul that illustrate the uneasy interactions that stem from past anti-communist education as well as the subsequent erasure of social memory about North Korea as part of Korean culture.